1983
DOI: 10.1111/j.1365-3024.1983.tb00737.x
|View full text |Cite
|
Sign up to set email alerts
|

The athymic nude rat. IV. Immunocytochemical study to detect T‐cells, and immunological and histopathological reactions against Trichinella spiralis

Abstract: The anti-parasite response was investigated after oral infection of athymic nude (rnu/rnu) rats and heterozygous (+/rnu) littermates with 1000 muscle larvae of Trichinella spiralis. No IgM, IgG and IgE antibodies were detected in serum of rnu/rnu rats. Expulsion of adult worms from the small intestine was prolonged (worms were nearly all expelled at days 14 and 91 in +/rnu and rnu/rnu rats respectively). The yield of muscle larvae in the carcasses of nude rats at day 91 was 33 times higher than in +/rnu rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 23 publications
(11 reference statements)
2
22
0
Order By: Relevance
“…Sections 2 to 3 m thick were stained with hematoxylineosin in accordance with standard procedures and microscopically examined. The microscopic analysis was based on histopathological indices as described elsewhere (12,35).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sections 2 to 3 m thick were stained with hematoxylineosin in accordance with standard procedures and microscopically examined. The microscopic analysis was based on histopathological indices as described elsewhere (12,35).…”
Section: Methodsmentioning
confidence: 99%
“…The same section was scored for the severity of the inflammatory reaction around the encysted larvae based on the distribution of different cell types in the infiltrate and the number of inflammatory cells (35). A score of 0 indicates no inflammation, a score of 1 indicates minimal inflammation, a score of 2 indicates slight inflammation, a score of 3 indicates moderate inflammation, and a score of 4 indicates marked inflammation.…”
Section: Methodsmentioning
confidence: 99%
“…Mastocytosis in T. spiralis infection is T cell dependent (39,40). Because intestinal mastocytosis was not required for rapid expulsion, and knowing that IgG2c mediates rapid expulsion in rat pups and can be produced in a T cell-independent manner (41), we tested the requirement for T cells in rapid expulsion by challenging parenterally infected, T cell-deficient rats.…”
Section: Parenteral Immunization Generates a T Cell-dependent Mucosalmentioning
confidence: 99%
“…17 Using athymic mice, research has shown that these intestinal mast cells are thymus-dependent. 1y, 26 Since proliferation of globule leukocytes has been demonstrated to be thymus-independent,18s20 intestinal mast cell origin seems unlikely. These and additional studies lend support to the earlier hypothesis that globule leukocytes represent a unique population of mesenchymal origin.…”
mentioning
confidence: 99%